EFEK POLUTAN TERHADAP FISIOLOGIS MAKROINVERTEBRATA SUNGAI : REVIEW - Miftahul Khair Kadim; Diana Arfiati (EnviroScienteae, 2022)
Contaminants sourced from numerous anthropogenic activities threaten a river ecosystem continuously. Anthropogenic modification alters water quality and affects aquatic biota life. Most of the pollution of the aquatic environment comes from chemical materials such as heavy metals, fertilizers, pesticides, and plastics. Heavy metals are the most dangerous pollutants as they are toxic, carcinogenic, biomagnifying, and bioaccumulative. Pollution affects the survival of aquatic biota, including macroinvertebrates. The sedentary nature of macrozoobenthos makes it to be contaminated with ease, which then affects its survival. Currently, the damaging impact of pollutants on the physiology of macrozoobenthos has been reported in several studies though it is still limited to the use of particular families. This review aims to inform the physiological impacts caused by pollutants on the macrozoobenthos community that lives along the river from upstream to downstream. Pollutants trigger disturbances in physiological functions, which are termed oxidative stress. Macrozoobenthos perform a series of mechanisms, including producing enzymes as the primary defense.